Comunicação, memória e lugar: análise das interações do grupo do FacebookRavena e suas memórias" - Nathália Edwirges Amado (2017)
This study looks at contemporary communities in media environments and aims to understand how the process of re-signification of the place occurs through the fragments of memory that are shared by individuals in interactions in a digital social media. So we analyse a Facebook group called "Ravena e suas memórias", created by residents of the Ravenadistrict, Sabará - Metropolitan Region of Belo Horizonte / MG - was created to promote the sharing of images, texts and archives about the place and its population. Starting from the idea that there are no separate ambiences, in this research it is considered that "virtual" and "real" are instances that make up the dynamicity of contemporary life. Based on the concept of community, as the ideal of sociability sought until today, the main premise is that the relationship between man and space is the base of the conformation of the place. Implicated directly to the studied object is the concept of memory, since it is a group in social media withexclusive scope of sharing of memories. In order to observe aspects of the ambiences involved, the chosen methodology unites different analyses. First, a content analysis of the posts, with the observation of the discussions and themes; and, a later analysis of the interactions flows, with information gathering of the Facebook platform, highlighting thespecificities of the object. In the second phase of the methodology, the data obtained by online questionnaire were analysed, and the analysis of six in-depth interviews with some actors of "Ravena e suas memórias". At the end of the procedures, some dimensions were highlighted that demonstrate the conformation of the feeling of love to the place, and in the research we opted to examine the dimensions of nostalgia and belonging. These dimensions demarcate the affective relationship of the subjects with the local memory, and the interactions show tracesof the signification of the place, both in the digital environment and in the physical community. Communication appears as the main agent in this process. Thus, the group plays an important role in the process of (re) configuring the locality, since it acts directly on the dimensions of belonging, captivating a nostalgia directly implicated in topofilia, however,although there is value, the initiative leaves unexplored potentialities.